Brez digitalizacije in prenosa zapuščinskih postopkov bo vse trajalo samo še dlje - Majcen, Manca (Pravnik, 2025)
It is now 30 years since notarial services were re-introduced in the Republic of Slovenia. To mark the anniversary, the Notary Chamber of Slovenia (NCS) held a ceremonial event attended by Slovenian and foreign guests, legal experts and others. After a review of the milestones that have shaped Slovenian notarial practice over the past three decades, participants heard addresses by the President of the NCS, notary Dr Bojan Podgoršek, the Minister of Justice, Andreja Katič, and several other speakers. The programme continued with a round-table discussion on the still-untapped potential of notarial services in Slovenia and the presentation of awards for outstanding contributions to their development. Among the opportunities identified, the transfer of undisputed inheritance proceedings to notaries featured prominently. Doing so would ease the workload of the courts—relieving at least 40 judges—while accelerating the resolution of cases and making the process more accessible for the parties involved. Public expenditure would fall and private costs would remain unchanged. A further opportunity lies in performing notarial acts in a digital environment. For three years Notarial Act has contained a legal basis for issuing electronic notarial instruments prepared via a secure, real-time video link with a notary. However, implementation is still pending because the Ministry of Justice has yet to select a provider for the necessary information and video-communication system that would enable remote drafting of notarial documents.
Keywords: digitalisation; digitalizacija; notar; notarial services; notariat; notary public; probate procedures; razbremenitev sodišč; relief of the burden on courts; zapuščinski postopki